Adsorption and wettability of extended anionic surfactants with different PO numbers on a polymethylmethacrylate surface. Issue 26 (16th June 2021) - Du, Yuechun; Zhou, Zhao-Hui; Gao, Ming; Han, Lu; Zhang, Lei; Yan, Feng; Wang, Mingxia; Zhang, Lu
Abstract : The number of propylene oxide (PO) unit plays crucial role in controlling the wettability of surfactants on the surface of polymethylmethacrylate (PMMA). Abstract : To investigate the effect of the number of propylene oxide (PO) units on the wettability of surfactants, the wettability of isomeric dodecyl(polyoxyisopropyl)7 sulfate (S-C12 PO7 S) and isomeric dodecyl(polyoxyisopropyl)13 sulfate (S-C12 PO13 S) on the surface of polymethylmethacrylate (PMMA) was investigated. The adsorption behavior on the PMMA surface was analyzed by measuring the surface tension and the contact angle. It is found that the PO group may form hydrogen bonds with the PMMA surface, thus facilitating the hydrophobic tails pointing to the aqueous phase. Moreover, the steric effect of the PO group benefits the formation of semi-micelles above the critical micelle concentration (CMC). Surfactant molecules adsorb on the PMMA surface by polar adsorption below the CMC with hydrophobic tails towards the water. Therefore, the PMMA surface is modified to be more hydrophobic. However, the sodium dodecyl sulfate (SDS) surfactant with no PO unit does not have hydrophobic modification ability on the PMMA surface. Below the CMC, the adsorption amounts of the S-C12 PO7 S and S-C12 PO13 S surfactants at the solid–liquid interface were approximately 1/3 of those at the air–liquid interface. Interestingly, the adsorption behavior changes when the concentration of the surfactants is around the CMC. The hydrophilic heads of the surfactant molecules will point to water, and the surfactant molecules will form semi-micellar aggregates on the PMMA surface. Therefore, the PMMA surface is modified to be hydrophilic above the CMC. What's more, both the hydrophilic modification ability and hydrophobic modification ability of the S-C12 PO13 S surfactant are stronger than those of the S-C12 PO7 S surfactant. This means that the number of PO units will affect the wettability ability of the surfactants. Therefore, the S-C12 PO13 S surfactant possesses smaller contact angles than the S-C12 PO7 S surfactant at high concentrations.